Calculus for Cognitive Scientists Higher Order Models and Their Analysis - Peterson, James K. (Cognitive Science and Technology, 2016)
This book offers a self-study program on how mathematics, computer science and science can be profitably and seamlessly intertwined. This book focuses on two variable ODE models, both linear and nonlinear, and highlights theoretical and computational tools using MATLAB to explain their solutions. It also shows how to solve cable models using separation of variables and the Fourier Series.